Using the Self-Advocacy Strategy to Support Middle School Students With EBD. (August 2022) - Balint-Langel, Kinga; Riden, Benjamin S.
Self-advocacy skills enable active student involvement in the Individualized Education Program (IEP) planning process. However, some students with emotional and behavioral disorders (EBD) lack appropriate self-advocacy skills and may require specific instruction in how to prepare for and participate in their own IEP. Special educators may have limited knowledge and skills to foster the self-advocacy skills of students with EBD. Therefore, this article focuses on a research-based strategy, the Self-Advocacy Strategy (SAS), that can be used by educators to effectively promote students' self-advocacy skills. Research support and a detailed overview and guidelines on how educators can implement the SAS in their classrooms are included.